2023
DOI: 10.3389/fbioe.2023.1261022
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive technologies for heart failure, systolic and diastolic dysfunction modeling: a scoping review

Sona M. Al Younis,
Leontios J. Hadjileontiadis,
Cesare Stefanini
et al.

Abstract: The growing global prevalence of heart failure (HF) necessitates innovative methods for early diagnosis and classification of myocardial dysfunction. In recent decades, non-invasive sensor-based technologies have significantly advanced cardiac care. These technologies ease research, aid in early detection, confirm hemodynamic parameters, and support clinical decision-making for assessing myocardial performance. This discussion explores validated enhancements, challenges, and future trends in heart failure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…NICaS ® can assess cardiac function and provide information on several parameters, like cardiac output (CO), cardiac index (CI), and systemic vascular resistance (SVR). NICaS ® -measurement procedures and validation studies compared to Swan-Ganz-and PICCO ® -catheterization techniques were reported recently [14][15][16][17][18].…”
Section: Nicas ® Device and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…NICaS ® can assess cardiac function and provide information on several parameters, like cardiac output (CO), cardiac index (CI), and systemic vascular resistance (SVR). NICaS ® -measurement procedures and validation studies compared to Swan-Ganz-and PICCO ® -catheterization techniques were reported recently [14][15][16][17][18].…”
Section: Nicas ® Device and Proceduresmentioning
confidence: 99%
“…Intensified clinical and biomarkerbased patient monitoring and early re-evaluation of therapeutic strategies are crucial for therapy management and can favorably influence outcomes. Therefore, supporting straightforward diagnostic tools, such as non-invasive bedside bio-impedance monitoring (NICaS ® NIMedical, Israel Advanced Technology Industries, Hertzliya Pituach 4676672, Israel), provides an accurate and approved method to obtaining hemodynamic parameters in acute and chronic HF [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous cardiovascular conditions, such as atrial fibrillation, myocardial infarction, congestive heart failure, and premature contractions in the atria or ventricles can be identified through the analysis of ECG data [20][21][22][23][24][25]. As a result, the automatic and precise analysis of ECG data has emerged as a prominent area of study, particularly with the utilization of artificial intelligence (AI) tools.…”
Section: Introductionmentioning
confidence: 99%
“…ECG is one of the most widely used non-invasive diagnostic tools for tracking the physiological activities of the heart throughout time. Many cardiovascular disorders, including atrial fibrillation, myocardial infarction, premature contractions of the ventricles or atria, and congestive heart failure, can be diagnosed with the help of ECG data [20][21][22][23][24][25]. Consequently, automatic and accurate ECG data analysis has become a popular study area, especially using artificial intelligence (AI) tools.…”
Section: Introductionmentioning
confidence: 99%